IMPROVEMENT OF A TECHNIQUE OF WORK INCENTIVES OF NOVATORS AND INNOVATORS IN THE INNOVATIVE COMPANIES - Tatiana A. Doroshevskaya (Вестник Северо-Кавказского федерального университета, 2022)
Article is devoted to questions of research of ways and methods of stimulation and motivation of the personnel of the innovative enterprises. It is offered the instrument of motivation by material incentives for the personnel of the innovative enterprise.